Ectoparasitos associados a aves de um fragmento de Floresta Estacional Decidual no Rio Grande do Norte, Brasil - Silva, Honara Morgana da (2013)
This study to aimed investigate the community of ectoparasites associated with birds in the Mata do Olho D água, in the municipality of Macaíba, Rio Grande do Norte (RN), Brazil, its structure and the ambiental and hosts influential variables on it, and to verify microhabitats preferences by species of chewing lice and feather mites. We examined 172 individuals belonging to 38 species of Passeriformes and non-Passeriformes. 12 new geographic records are reported and 11 host-parasite associations not yet known for chewing lice and feather mites species. Significant relationship was found between the abundance of chewing lice and the variables total length (r = 0.29, p <0.05) and exposed culmen (r = 0.38, p <0.05) of the hosts. A principal component (PC1) accounted for 90.1% of the hosts morphological variation was significantly influential on the abundance of chewing lice (p <0.05), indicating that the morphological characteristics of the hosts may be positively influencing the abundance of these ectoparasites. Significantly higher frequency of individuals with high loads of chewing lice was detected during the dry period (x ² = 8.5, p <0.05), corroborating studies that propose that birds of arid environments suffer as much pressure as those of parasitic humid environments. Analyses of null models of co-occurrence and niche overlap showed a high degree of structure in the feather mites and chewing lice assemblies, when compared with other groups, and preferences in the use of microhabitats by taxa identified. These results corroborate ecological theories in host-parasite systems, contribute to the knowledge of ectoparasites associated with neotropical birds, and the need for experimental studies, as well as further deepening the biology of these arthropods